Pattern-forming nanoprecipitates in NiTi-related high entropy shape memory alloys. (September 2020) - Hinte, Christian; Barienti, Khemais; Steinbrücker, Jan; Gerstein, Gregory; Swider, Mark Alan; Herbst, Sebastian; Eggeler, Gunther; Maier, Hans Jürgen
Abstract: The microstructure and the fracture behavior of TiZrHfCoNiCu high entropy shape memory alloys with two different compositions were investigated. An unusual microstructure featuring pattern-forming nanoprecipitates was observed in dendritic and the interdendritic regions of both alloys. The unique higher-level order of these precipitates does not follow concentration gradients but is influenced by homogeneity and mechanical stress. The results also demonstrate that high entropy alloys are not necessarily homogeneous single-phase solid solutions. Moreover, it appears that solid solution strengthening as the primary mechanism also has to be questioned. Graphical abstract: Image, graphical abstract